2000
DOI: 10.1007/s002590000277
|View full text |Cite
|
Sign up to set email alerts
|

Infection imaging using whole-body FDG-PET

Abstract: The purpose of this study was to evaluate fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) for the detection of soft tissue and bone infections. Forty-five PET examinations in 39 patients (26 male, 13 female, age range 27-86 years) with suspected infectious foci were examined with whole- or partial-body PET scans using FDG. Twenty-seven scans were done in patients with soft tissue and 18 in patients with bone infections. Corrected and uncorrected transaxial PET images were acquired. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
117
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(126 citation statements)
references
References 15 publications
2
117
0
6
Order By: Relevance
“…Rectal involvement was present in our case, which contributed to the suspicion of malignancy. 18 F-FDG PET/CT has been used in the evaluation of a large variety of infectious processes, including abscesses [5]. On PET/CT, abscesses often exhibit a hypometabolic center surrounded by an intensely FDG-avid rim [24,25], although they can also exhibit solid uniformly intense FDG uptake throughout, as in our case [26].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Rectal involvement was present in our case, which contributed to the suspicion of malignancy. 18 F-FDG PET/CT has been used in the evaluation of a large variety of infectious processes, including abscesses [5]. On PET/CT, abscesses often exhibit a hypometabolic center surrounded by an intensely FDG-avid rim [24,25], although they can also exhibit solid uniformly intense FDG uptake throughout, as in our case [26].…”
Section: Discussionmentioning
confidence: 74%
“…Atypical or equivocal cases often require further imaging with computed tomography (CT) or magnetic resonance imaging (MRI); however, CT and MRI findings can also be non-specific and TOA has been mistaken for ovarian tumors on CT as well as MRI [4]. 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT has been successfully used to image a wide variety of infectious processes, including abscesses [5]; however, the PET/CT literature on TOA is very limited. It is important for PET/CT readers to be aware of this benign differential diagnosis of bilateral FDG-avid adnexal masses, even in the context of CT or MRI findings suspicious for malignancy, as this may impact clinical management with consideration to important patient-related issues, such as maintaining fertility in premenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…However, lymphocytes, macrophages, neutrophils, and fibroblasts also avidly take up 18 F-FDG, particularly under activation conditions (8). Thus, primary inflammatory diseases (such as sarcoidosis) as well as infectious diseases (such as tuberculosis or aspergillosis) can be imaged by means of 18 F-FDG-PET (9).…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed decreased glucose metabolism in the ipsilateral caudate 3-7 months posthemispherectomy, with recovery nearing pre-surgical levels in scans acquired 12-30 months posthemispherectomy and support a role for the caudate nucleus in compensatory changes following hemispherectomy (Chugani and Jacobs, 1994). There is a great deal of evidence that inflammatory processes can lead to increased FDG-PET uptake in animal studies (Ishimori et al, 2002) and in human disease (Bakheet and Powe, 1998;Brudin et al, 1994;Guhlmann et al, 1998;Stumpe et al, 2000). If striatal inflammation were responsible for increased AMT uptake in the current study, then we would expect a similar temporo-spatial pattern of FDG and AMT uptake in the ipsilateral striatum.…”
Section: Discussionmentioning
confidence: 88%